Saberes compartilhados: rodas de conversa e dialogicidade na educação física escolar - Gouveia, Samantha Lopes (2024)
The aim is to understand the systematization of conversation circles in Physical Education classes from a reflective, problematizing and dialogical perspective, using participatory planning, discussing themes of social dilemmas, which allow establishing strategies focused on dialogue, questioning and argumentation. The research problem is to analyze whether conversation circles can be relevant to favor, in Physical Education classes, students who are more reflective in relation to social dilemmas. In this research, it was proposed to apply and analyze the pedagogical proposal of Conversation Circles with the collaboration of residents of the UFC Pedagogical Residency Program, to 8th year students at the municipal school Maria Helenilce Cavalcante Leite Martins, in Fortaleza, teacher-researcher’s workplace. The implementation of the Conversation Circles was conceived as an opportunity for the teacher, residents and students to engage in meaningful discussions of different social dilemmas, encouraging critical reflection and the collective construction of knowledge. By adopting a non- hierarchical approach, the focus was on valuing the diversity of perspectives and promoting an inclusive and participatory environment, in which all participants could contribute significantly to the process of reflection, dialogue and learning. We created and monitored the development of Conversation Circles, throughout the 2023 school year, with three groups of students in the 8th year of Elementary School. The general objective was to analyze, from the perspective of students and residents, the implementation of a pedagogical proposal based on conversation circles in Physical Education classes, for a more reflective and dialogical process of student learning. The specific objectives were: Discuss the relevance of systematizing conversation circles in Physical Education classes; Describe the process of implementing conversation circles in school Physical Education classes and Verify the potential/limits of conversation circles in Physical Education classes as a didactic-methodological strategy for addressing students' social issues.The theoretical-conceptual contributions were diversified, due to the integration of research between education, physical education, relationship with knowledge, reflection and dialogicity and participatory planning and systematization, and were anchored in authors such as: Venâncio (2014), Sanches Neto ( 2014), Silva (2011), Darido (2020), Freire (2001), Charlot (2007), among others. In this research, a qualitative approach and a methodological strategy with a descriptive and exploratory approach. An exploratory questionnaire was applied to students and residents. The triangulation of the data produced was interpreted through thematic analysis based on the categorization of information from the questionnaires. The results obtained showed the positive impact of conversation circles on the personal and professional training of those involved, highlighting their importance in promoting a more collaborative, inclusive, participatory and transformative education. By creating opportunities for open dialogue and critical reflection, the conversation circles contributed to the development of essential skills, such as critical thinking, empathy and mutual respect, preparing students to face the challenges of the contemporary world.